The CBS Domain: Its Structure, Ligand Binding, and Emerging Role in Regulation - Scarlata, David (McGill Science Undergraduate Research Journal, 2017)
Background: Cystathionine β-synthase (CBS) domains are structurally conserved motifs that are present in the proteomes of species from all kingdoms of life. Signifying their importance are the hereditary diseases resulting from mutations within the CBS sequence. They are usually encoded in tandem within a plethora of non-functionally related cytosolic or transmembrane proteins, often intramolecularly dimerizing to afford what is known as a CBS pair or Bateman module. It is also known that these CBS pairs can further multimerize to form higher-order assemblies, which have functions that remain to be elucidated. Moreover, a wide range of adenosyl ligands, divalent cations and nucleic acids have been documented to bind CBS domains and induce conformational changes to the larger protein in which they reside, thus suggesting their involvement in protein regulation in response to intracellular energy status. Methods: This review was written based on the existing data currently available in the literature and included findings from 44 papers. Selection of papers was based on those that provided up-to-date information on the structural characteristics of CBS domains and their involvement in protein regulation. Summary: This review aims to conceptualize the architectural characteristics of CBS domains, the structural basis of ligand binding, and its involvement in the regulation of protein function.